Poland – Economic Development Level in Comparative Perspective, 1950-2005 - Ryszard Rapacki (ZBW - Leibniz Information Centre for Economics; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2006)
The aim of the present paper is to show the most aggregate quantitative results of systemic transformation in Poland to date, in terms of changes of country's absolute and relative development levels, i.e. its GDP per capita compared to other countries, in particular fellow transition economies and UE members. The analysis consists of four parts. In the first part, to shed more light on the present comparative position of Poland on world development ladder, a historical perspective is provided. Between 1990 and 1989, i.e. during the period of command economy, Poland witnessed a real divergence trend. widening the development gap not only towards Western industrialized economies but also vis-à-vis fellow socialist countries. In part two the process of fast catching up in Poland vis-à-vis both groups of economies between 1990 and 2005 is illustrated with data on economic growth and indices showing the relative development levels. During this period Poland was the fastest growing transition economy while also displaying higher GDP growth rates compared to the UE-15 average. Part three shows the present comparative position of the Polish economy in the world and in the enlarged European Union, both in terms of economic potential (total GDP) and development level (GDP per capita). The concluding part summarizes the findings of the paper and sketches the prospects of the real convergence process of the Polish economy towards the future development level in the EU-15 countries.
Conference: International Conference in memory of George Blazyca: “Reinventing Poland”, University of Paisley, Glasgow, 10-11 November 2006; Additional information: Paper prepared for the international conference in memory of George Blazyca: “Reinventing Poland”, University of Paisley, Glasgow, 10-11 November 2006.
Keywords: P2; P5; 330; transition; poland; Transition countries; Poland